2013
DOI: 10.1530/rep-12-0319
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol supports in vitro development of bovine early antral follicles

Abstract: Antrum formation and estradiol (E 2 ) secretion are specific features of oocyte and granulosa cell complexes (OGCs). This study investigates the effect of E 2 on the in vitro development of bovine OGCs derived from early antral follicles as well as on the expression of genes in granulosa cells (GCs). The supplementation of culture medium with either E 2 or androstenedione (A 4 ) improved the in vitro development of OGCs and the nuclear maturation of enclosed oocytes. When OGCs were cultured in medium containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 43 publications
2
30
1
Order By: Relevance
“…A recent report showed that E 2 improved antrum formation of bovine OGCs cultured in vitro, and gene expression between OGCs cultured with high E 2 and those with low E 2 . The use of NGS showed that most of the marker genes that are associated with the large healthy follicles were expressed at higher levels in granulosa cells of OGCs cultured with E 2 than in those cultured without E 2 [24]. In the present gene expression analysis, the genes that are associated with healthy large follicles were expressed at lower levels in OGCs of aged cows.…”
Section: Discussionmentioning
confidence: 45%
See 3 more Smart Citations
“…A recent report showed that E 2 improved antrum formation of bovine OGCs cultured in vitro, and gene expression between OGCs cultured with high E 2 and those with low E 2 . The use of NGS showed that most of the marker genes that are associated with the large healthy follicles were expressed at higher levels in granulosa cells of OGCs cultured with E 2 than in those cultured without E 2 [24]. In the present gene expression analysis, the genes that are associated with healthy large follicles were expressed at lower levels in OGCs of aged cows.…”
Section: Discussionmentioning
confidence: 45%
“…Ovaries of Japanese Black Cows (Bos taurus) were collected from a slaughterhouse, maintained at 30°C in phosphate-buffered saline (PBS) containing antibiotics, 10 mM sucrose, and 10 mM glucose, and transported to the laboratory within 4 h. The medium used for the in vitro culture of OGCs collected from EAFs was based on a previous report [24] with a slight modification; our medium contained 0.1 or 10 μg/mL 17β-estradiol. TCM-199 medium supplemented with 10 % FCS (570H, ICN; Costa Mesa, CA, USA) and antibiotics was used for in vitro maturation (IVM medium).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Estradiol and progesterone are major hormones that regulate ovarian growth and physiological function 3134 . In mammals, circulating estrogens are mainly produced by the granulosa cells, and required for the development of secondary sex characters in females 35 .…”
Section: Discussionmentioning
confidence: 99%